What do we need to address when we treat neglected Monteggia fracture in children - Yi, Yangfei; Liu, Can; Xu, Zheng; Xie, Yuyin; Cao, Shu; Wen, Jie; Jian, Xiaohong; Li, Yufei (Frontiers in Pediatrics, 2024)
Monteggia fracture is a relatively uncommon injury in pediatric patients, accounting for less than 2% of forearm fractures, characterized by a combination of ulna fracture and radial head dislocation. Neglected Monteggia fractures define as those that have not received treatment within 3 weeks. In children, ulna fractures are easily diagnosed while radial head dislocation may be overlooked, necessitating open reduction after neglecting the Monteggia fracture and potentially causing additional trauma to the child. This study aims to review the pathological characteristics of neglected Monteggia fractures based on the length ratio of the ulna and radius, relative positions between the proximal ends of the ulna and radius, the integrality of annular ligament and the pathological change of proximal radioulnar joint. The findings will provide valuable insights and guidance for managing neglected Monteggia fractures.